Gaya Kepemimpinan Situasional, Budaya Organisasi, Tingkat Pendidikan, Motivasi dan Kinerja Karyawan - Sudeva, I Gusti Agung Oka; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2021)
In 2019-2020, 21.4 percent of the cooperatives were dissolved. The increased dissolution of cooperatives is thought to be due to poor cooperative management and employee performance. This study aims to determine the effect of situational leadership style, organizational culture, educational level, and motivation on employee performance of Klungkung Regency Cooperative with a quantitative approach. Data collection was carried out through a questionnaire. The population is all cooperatives located in Klungkung with cooperatives in Klungkung as samples through purposive sampling. The analysis technique used is multiple linear regression. Results show that situational leadership, organizational culture, education level and motivation have a positive effect on employee performance. These results support attribution theory and organizational behavior theory. Keywords : Situational Leadership; Organizational Culture; Education Level; Motivation; Employee Performance